810 Incidence and determinants of permanent pacemaker implantation after transcatheter aortic valve replacement. (8th December 2021) - Bellantoni, Antonio; Sorrentino, Sabato; Boccuto, Fabiola; Carabett, Nicole; Giordano, Salvatore; Cacia, Michele Antonio; Polimeni, Alberto; Leo, Isabella; Varano, Ylenia; Augusto, Florinda Maria; Mongiardo, Annalisa; De Rosa, Salvatore; et al.
Abstract: Aims: conduction disturbances requiring pacemaker implantation (PPM) are among the most common complications in patients undergoing transcatheter aortic valve replacement (TAVR). Introduction in clinical practice of a new generation of TAVR devices is contributing to a significant reduction in procedural complications. However, limited data is available regarding PPM implantation after TAVR with the latest available devices. Accordingly, in this analysis we aimed to investigate the incidence and risk factors for new permanent pacemaker implantation after TAVR according to the type and diameter of valve implanted. Methods: Patients who underwent TAVR at our Institution from September 2008 to November 2020 were included in this analysis. Out of 407, 38 (9.3%) were excluded because they already presented a PPM/ICD, received only balloon angioplasty or for procedural unsuccess. The independent association between baseline clinical and procedural variables and the occurrence of PPM implantation was investigated with cross-sectional logistic regression analysis. Results: Out of 368 TAVR procedures included in the final analysis, 89 (24.2%) required in-hospital PPM implantation. No differences were observed for age and common cardiovascular risk factors between groups. Among procedural variables, patients requiring PPM had lower left ventricular ejection fraction (LVEF) and experienced a longer intensive care unit stay. Valve types used were Corevalve n  = 98 (26.6%) (first-generation devices), Evolute R, n  = 191 (51.9%), Evolute Pro, n  = 3 (1.1%), Portico n  = 2 (0.5 %), or Sapien 3, n  = 73 (19.8%) (second-generation devices). Clinical and procedural correlates of PPM implantation were depicted in Figure . Of note, compared to the first generation of self-expandable devices, the second generation is associated with a lower risk of PPM implantation, albeit non-significant for the subgroup of second generation self-expandable devices. Finally, valve diameter was also an independent predictor of PPM implantation Conclusions: PPM was required in 24.2% of patients who underwent TAVR with first- and second-generation balloon or self-expandable valves. For instance, in our population, second-generation TAVR devices were associated with a lower risk of PPM implantation compared to the previous generation. However, further investigations are warranted to assess the impact of new implantation techniques and valve technology on such an important outcome.